Epistemological obstacles in texts in magazines of Scientific Disclosure (Research, Society and Development, 2020)
The scientific disclosure is a means of science diffusion to the general public which utilizes different resources, such as magazines, television, internet, among others. These resources of disclosure present an accessible language that is easily comprehended. Many of them make use of analogies, metaphors and images to facilitate the explanation of a concept and to improve the fluidity of reading. Therefore, this article intends to analyse the presence of epistemological obstacles on Galileu, Scientific American Brasil and Superinteressante magazine texts on the theme of Radioactivity. The time interval proposed to cover this analyses was between the years of 2014 and 2019, obtaining a total of 14 texts. From the analyses of these texts were found the following epistemological obstacles: animist, verbal, unitary and pragmatic, being that verbal had the most occurrence. We believe that the presence of these obstacles in articles may contribute to science debates.